Implementasi Teknologi Tepat Guna Alat Penyiraman Otomatis Sebagai Penunjang Ketahanan Pangan Keluarga Berbasis Pertanian Urban - Anggi Indah Yuliana; Achmad Agus Athok Miftachuddin; Rohmat Hidayat; Rindhi Dwi Fibrianti; Erfan Nur Huda; Ziyyana Fitra; Yoga Firmansya (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Urban farming is a rapidly evolving concept in communities where families in residential areas are beginning to play a role in local food production. The implementation of appropriate technology proves to be a highly relevant solution to support urban farming. The goal of this program is not only to provide concrete solutions to the issues faced by partners but also to enhance the benefits of existing assets and potential in the Murukan village community, focusing on improving urban farming productivity, resource conservation, and providing education and empowerment to partners. The Asset-Based Community Development (ABCD) method is the approach used in the implementation of this community service program, with stages including: (1) Identifying community needs and potentials, (2) Designing an automatic watering tool, (3) Manufacturing and testing the tool, (4) Training, implementation, and (5) Joint evaluation. The results of this program show an increase in basic knowledge, reaching a 50% improvement from previously limited levels. The practical abilities of partners, which were previously very limited, progressed by 60%, indicating that partners can follow team instructions better. Technical skills of partners also showed significant improvement with a 70% percentage increase. Partner confidence and previously low productivity improved by 40% and 55%, respectively, after participating in this program. The efficiency of tool usage became more effective, with a 65% percentage increase. There was a 55% increase in productivity from the previously low category. Overall, the percentage progress after participating in this program indicates that the program is acceptable and runs well.